How general practitioners and aged care workers perceive incidences of elder abuse - Howrie, Paul (2000)
As the Australian population is expanding and ageing, there is an associated need for a focus to be placed on the Individual rights of elderly people, and for the general populus to be made more aware of areas related to our older generation. Elder abuse, as an area of concern, developed as an offshoot of investigations into child abuse and general domestic violence, and initially surfaced in the 1970s and 80s. Some sections of the medical profession were made specifically aware of the problem initially in 1975, through a letter that was sent to the British Medical Journal. However, throughout some of the literature, GPs have been criticised about their level of awareness of the issue of elder abuse, and for their lack of involvement in this area. The purpose of this study was to explore how General Practitioners and Aged Care workers perceive incidences of elder abuse. Due to the limited amount of research which has been undertaken on elder abuse within Australia, the study looked at exploring the issue rather than trying to measure its cause, or trying to identify the extent of the problem. The study investigated the perceptions of general practitioners (GPs) toward the area of elder abuse, and looked further to explore how general practitioners were perceived by aged care workers. The approach used for data collection consisted of circulating 100 mailed out questionnaires to general practitioners within metropolitan Perth, and follow up face-to-face interviews with some of the respondents to this questionnaire. Additionally, face-to-face interviews were also held with key informants who worked in the aged care industry, to ascertain their perceptions of elder abuse. The mailed questionnaires were analysed by adding the frequencies of responses given to each question. The data from the face-to-face doctor interviews and the key informant interviews were transcribed verbatim from the tape recordings and then assessed by looking for consistent regularities from each response made, therefore using a cross-case analysis. From this analysis, patterns emerged in the data, from which themes were developed. The recommendations from the data suggest that a clear and concise definition of elder abuse needs to be developed, to assist in clearly Identifying the prevalence of the problem. The data further recommended the need for an awareness campaign on the area of elder abuse to be undertaken. This should focus on raising the awareness of the possible characteristics of individuals who are vulnerable to being abused, as well as the characteristics of likely perpetrators of abuse. This study also recommended that a coordinated approach to dealing with the area of elder abuse should be developed, which should include the development of specific roles that should be undertaken by professional and non-professionals. Training of people across the Human Services field in the area of elder abuse, and in particular, GPs, social workers and paraprofessionals who work with elderly people, was identified as a recommendation of the study. Areas of training should include: awareness of the problem's existence; providing people with the required skills to detect cases of abuse; providing insight to referral agencies who may be able to assist; having a clear and exhaustive list of interventions to use to assist with addressing the problem; and having knowledge of the characteristics that abused individuals, and perpetrators are likely to have. This study also Identified that more research is required to ascertain if the amount of time which GPs spend with elderly people, is sufficient for them to identify cases of elder abuse, and if the allocated time from Medicare is adequate for GPs to Identify elder abuse